Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

Mental illness as social product or social construct: a contradiction in feminists’ arguments? - Busfield, Joan (Sociology of Health & Illness, 2008)
Feminists have been taken to task for suggesting both that the higher level of mental illness observed in women is a consequence of the oppression they face - an oppression which drives them into madness and mental disorder - and also that the concept of mental illness is a social construct inappropriately and incorrectly applied to women by a patriarchal order as a means of social control. This paper examines this supposed contradiction and the ideas that underly the contrasting contentions. It argues that the two positions are not in fact incompatible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Le droit à l’avortement, une lutte exemplaire - Revue À bâbord ! - bâbord!, Revue À (2008)
Militante de longue date pour le droit à l’avortement, Louise Desmarais publie en 1998 La lutte pour le droit à l’avortement, histoire d’une bataille inachevée. Elle présente ici les principales caractéristiques et les moments forts, selon elle, de la lutte pour le droit à l’avortement au Québec.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; approches et analyses; avortement; canada; care; corps; cours; discipline; histoire; justice reproductive; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social

Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

S’approprier son corps et sa santé. Entretien avec Rina Nissim - Fussinger, Catherine; Rey, Séverine; Vuille, Marilène (Nouvelles Questions Feministes, 2006)
Parmi les personnes qui ont réellement fait avancer les choses et apporté des changements dans la vie de beaucoup de femmes, il y a Rina Nissim qui a oeuvré depuis son engagement au sein du MLF de Genève au début des années 1970 pour que les femmes se réapproprient leur corps et leur santé. Ce numéro de « Nouvelles Questions féministes » sur la santé consacre une bonne partie de ses pages à une discussion avec Rina Nissim. Cette militante du groupe « avortement » et self-help » du MLF genevois raconte comment elle est passée de l'école d'infirmière à une vie de militantisme et de voyages, avec la naturopathie pour bagage. Publiant des ouvrages sur la santé des femmes ayant eu un succès important tel que « Mamamélis », cette pionnière en Suisse ouvre le « dispensaire des femmes »fonctionnant sur un mode autogéré, suite à un voyage aux États-Unis, avec d'autres femmes infirmières psychologues et médecins. Les femmes vont alors trouver une alternative aux rapports de pouvoirs classiques des relations médecin-patient et aux médicaments traditionnels, dans un mouvement de prise de conscience et d'action sur leur propre corps. L'engagement international de Rina, en Amérique Central et en Inde principalement où elle s'installe cinq ans et coordonne différents projets, aura permis a de nombreuses femmes de se découvrir elles-mêmes et les autres, de se débarrasser de la honte et se rendre compte que la maladie est souvent liée à un positionnement social.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inde; justice reproductive; premier cycle; périodes historiques; racisme; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail; états-unis

Médicalisation de la ménopause, mouvements pour la santé des femmes et controverses sur les thérapies hormonales - Löwy, Ilana; Gaudillière, Jean-Paul (Nouvelles Questions Feministes, 2006)
Le traitement hormonal de la ménopause, présenté entre 1970 et 2000 par la majorité des experts comme capable d’accroître le bien-être des femmes mais aussi de prévenir des nombreuses pathologies liées au vieillissement féminin, a été déclaré en 2002 inutile et dangereux suivant un essai clinique nord américain, Women’s Health Initiative (WHI). En voie de conséquence, les prescriptions de ce traitement ont chuté dramatiquement entre 2002 et 2005. Cet article retrace les origines féministes de WHI, puis suit les conséquences de la publication de ses résultats aux États-Unis, en France et en Allemagne. En conclusion, il revient sur les tensions entre les rôles des femmes comme utilisatrices des hormones, comme expertes et comme militantes des mouvements pour la santé des femmes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; allemagne; amérique du nord; amériques; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

The scientific revolution and the death of nature - Merchant, Carolyn (Isis, 2006)
The Death of Nature: Women, Ecology, and the Scientific Revolution, published in 1980, presented a view of the Scientific Revolution that challenged the hegemony of mechanistic science as a marker of progress. It argued that seventeenth-century science could be implicated in the ecological crisis, the domination of nature, and the devaluation of women in the production of scientific knowledge. This essay offers a twenty-five-year retrospective of the book’s contributions to ecofeminism, environmental history, and reassessments of the Scientific Revolution. It also responds to challenges to the argument that Francis Bacon’s rhetoric legitimated the control of nature. Although Bacon did not use terms such as “the torture of nature,” his followers, with some justification, interpreted his rhetoric in that light.
Keywords: approches et analyses; capitalisme; discipline; environnement; projet charge mentale; santé; santé de la nature; sciences; sciences de l'environnement; sexisme; systèmes d'oppressions; thématiques; torture de la nature; violences; écoféminisme

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

La fabrique moléculaire du genre : hormones sexuelles, industrie et médecine avant la pilule - Gaudillière, Jean-Paul (Cahiers du Genre, 2003)
L’histoire des hormones sexuelles est le plus souvent discutée en référence à l’invention de la pilule dans les années d’après-guerre. La molécularisation des sexes a toutefois été beaucoup plus précoce, plus complexe et plus contradictoire que cette vision ne le laisse penser. Parce qu’elle a fait intervenir tout à la fois une recherche biomédicale de haut niveau, une industrie pharmaceutique puissante et la biopolitique du régime nazi, la configuration allemande offre un terrain privilégié pour interroger les dynamiques de cette fabrique moléculaire du genre. Centré sur les rapports entre biologistes, industriels producteurs d’hormones et médecins spécialistes de la reproduction, cet article aborde trois aspects différents de l’histoire des stéroïdes sexuels avant la pilule : l’idée d’un continuum des sexes biologiques et les discussions qu’elle a suscitées, la médicalisation de la stérilité féminine et de la ménopause, et les multiples usages de la testostérone.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; féminisme radical; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

L'engendrement des choses: des hommes, des femmes et des techniques - Chabaud-Rychter, Danielle; Gardey, Delphine (Histoire des sciences, des techniques et de la médecine, 2002)
"Le monde contemporain est marqué par une amplification des biens et des choses, des techniques et des artefacts ; toutes choses nous semblant à la fois ordinaires, évidentes et neutres. Cette modernité est rarement interrogée du point de vue des hommes et des femmes qui la vivent. Pourquoi en effet prêter des intentions aux choses? Elles participent de nos vies, pourvoient à nos besoins, nous soulagent de bien des tâches. Remettre en question la neutralité des techniques est pourtant une bonne façon de s'interroger sur les rapports sociaux de sexes, en se demandant pourquoi les femmes sont durablement exclues de certains domaines techniques ; quel pouvoir confère la maîtrise des techniques ; quel est l'enjeu politique et symbolique de cette maîtrise ; et, au bout du compte, comment les techniques contribuent à ordonner le social, et en particulier les relations sexuées."
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Gender equity and socioeconomic inequality: a framework for the patterning of women's health - Moss, Nancy E (Social Science & Medicine, 2002)
This paper explores the interrelationship of gender equity and socioeconomic inequality and how they affect women's health at the macro- (country) and micro- (household and individual) levels. An integrated framework draws theoretical perspectives from both approaches and from public health. Determinants of women's health in the geopolitical environment include country-specific history and geography, policies and services, legal rights, organizations and institutions, and structures that shape gender and economic inequality. Culture, norms and sanctions at the country and community level, and sociodemographic characteristics at the individual level, influence women's productive and reproductive roles in the household and workplace. Social capital, roles, psychosocial stresses and resources, health services, and behaviors mediate social, economic and cultural effects on health outcomes. Inequality between and within households contributes to the patterning of women's health. Within the framework, relationships may vary depending upon women's lifestage and cohort experience. Examples of other relevant theoretical frameworks are discussed. The conclusion suggests strategies to improve data, influence policy, and extend research to better understand the effect of gender and socioeconomic inequality on women's health.
Keywords: approches et analyses; projet charge mentale; ressource en ligne; santé; santé des femmes*; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences économiques

Policing the national body: Sex, race, and criminalization - Silliman, Jael Miriam; Bhattacharjee, Anannya; Davis, Angela Y.; Committee on Women, Population, and the Environment (South End Press, 2002)
Keywords: amériques; approches et analyses; corps; environnement; justice reproductive; maternité; nationalisme; racisme; régions géographiques; santé; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis